Local People Knowledge about Plant Trees Species Inside Tropical Forest of Tengger Ranupani - Setyo Ayu Hardyanti; Luchman Hakim (University of Brawijaya, 2014)
Degradation of tropical forests in Indonesia is known more widespread. The development of societyactivities is known to be very fast, thus it causes land degradation. An effort to make ecosystem reparation of the tropical forest through restoration becomes very important to be done. The success of these efforts cannot be separated from the local community factors. The purpose of this study is to determine rainforest woody plant species that are recognized, and utilized also knowing the public perceptions in tropical forest restoration. The method used is quantitative ethnobotany with estimatingthe significance of the plant based on the level of popularity herbs known and frequently used by the society. The data were analyzed using the Relative Frequency of Citations (RFC) and Relative Importance (RI). There are thirtyfive plants that are mentioned by society. Eighteen species are woody plants. The highest value of RFC from the interview are pine (Casuarina junghuhniana) that the value is 1. It is often used to fill the need as a building material and firewood. The smallest value of RFC is 0.07 randu bacin (Pittosporum moluccanum). It is caused of lacking knowledge of the type and the benefits of the plants. RI value or numbers of plants that are most frequently mentioned is fir that is at 3.56. Meanwhile, the smallest value of RI is randu bacin (Pittosporum moluccanum) of 0.31. The society’s perception of woody plants is quite well. The society knows the benefits of forest plants and the forest condition today. The society’s traditional knowledge in benefitting the plants is to be hereditary. So that society makes serious efforts to help the activity of forest restoration by planting vegetation. Keywords: degradation, forest, restoration, trees, utilization